Special features of radio interception of APCO P25 messages in Russia - Dmitry Sergeevich Silnov (Institute of Advanced Engineering and Science, 2016)
Many special forces in Russia use APCO P25 encoding while radio talks. Using google speech or yandex speechkit while decoding radio talks can give huge advantage. Search engines can index decoded text or knowledge base can be created.